Pengaruh Belanja Modal Terhadap Kesejahteraan Masyarakat - Endy Grade Tampubolon (Universitas Indraprasta PGRI, 2019)
This study aims to look at the effect of capital expenditure on the economic growth of districts/cities in Indonesia during the period 2014 to 2017 and see the impact of economic growth on community welfare which is proxied by the human development index number. Using the WarpPLS adopting a purposive sampling method, testing was carried out for 415 autonomous districts and 93 autonomous cities in Indonesia using data series 2014-2017. The results of this study indicate that capital expenditure has a positive effect on economic growth. Furthermore, economic growth has been proven to improve the welfare of the community.